Evaluation of Some Natural Feed Additive in Growing Chicks Diets - Abaza, I.M.; Shehata, M.A.; Shoieb, M.S.; Hassan, I.I. (International Journal of Poultry Science, 2008)
This study was conducted to evaluate the effect adding of Saccharomyces cerevisiae, Bacillus subtilis and Bacillus licheniform, black seed oil versus, virginamycin and zinc bacitracin to growing chick's diets at level of 0.1%, for each. Growth performance, digestibility, carcass treats, meat composition, serum blood constituents and economical efficiency of growing chicks were studied. A total of 180 unsexed one-day old chicks, were divided into 6 treatments of 30 chicks each in three replicates. The experiment was terminated when chicks were 12 weeks of age. The results showed that, addition of black seed oil, Saccharomyces cerevisiae and Bacillus subtilis and Bacillus licheniform in the experimental diets increased body weight, body weight gain. Chicks fed diets supplemented with black seed oil and virginamycin were significantly lower in their feed consumption. While, Chicks fed diet supplemented with saccharomyces cerevisiae consumed the highest amount of feed. The best feed conversion ratio was recorded with chicks fed diets contained black seed oil or virginamycin. All the treatments insignificantly affected dressing, giblets percentages, composition of breast Meats and blood serum constituents as compared with those of the control. Chicks fed diets supplemented with either black seed oil, virginamycin or Bacillus subtilis and Bacillus licheniform had significantly decreased abdominal fat percentages. The Addition of Saccharomyces cerevisiae, black seed oil and Bacillus subtilis and Bacillus licheniform significantly improved digestibility coefficient of dray matter and crude protein. The best relative economical efficiency was recorded by black seed oil flowed by virginamycin addition. It was concluded that black seed oil, Bacillus subtilis and Bacillus licheniform and Saccharomyces cerevisiae, could serve in growing chicks diets. However, further research is required to better understand the role of natural feed additives in poultry nutrition and their implications in human health.